Glove to Translate Sign Language - Sulakshana, Bodke; Gayatri, Alai; Dipali, Shinde; Sonali, Pawar (International Journal of Computer Sciences and Engineering, 2025)
This system describe talkable hand glove system which aims at translation of sign language to analyze text and voice. This system consists of a talk able glove that can be worn by a deaf/dumb person to facilitate the communication in real-time with other people. The system translates the hand finger motion to corresponding letters using IR sensors and a Microcontroller. Our main goal is to identify 26 alphabets and display text on the LCD. Once the text is obtained on the LCD then text to speech conversion operation is carried out and finally a voice output is obtained. Further, the text gain can also be viewed on a LCD or any portable hand held device. Our main aim is to set an interface between the Deaf or Dumb and normal people to improve the communication capabilities so that they can communicate handily with others. We mount IR sensor on the talk able hand glove and propose and efficient methodology to convert these sign languages. This system will simplify the communication of deaf or dumb people with people able to normal communications without the need of a human translator.